PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN DIMODERASI BUDAYA ORGANISASI (Studi Pada Guru SMP Di Kecamatan Comal Kabupaten Pemalang) - Cipto, 1352020038; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the influence of the competence and motivation of teachers to work on the performance of the organizational culture moderated. Population and sample were teachers SMP Comal District of Pemalang totaling 135 people from five (5) Junior High School, all members of the population used as a sample with saturated sampling technique. The research data is primary data obtained directly from the respondents to the questionnaire. The research method using SPSS for Windows version 21. The method of data analysis using Moderation Regression Analysis (MRA) type quasi moderator. From the test data and analysis conducted this study provide empirical evidence as follows: 1) Competence affect teacher performance Junior High School in District Comal Pemalang; 2) Work motivation affect the performance of teachers Junior High School in District Comal Pemalang; 3) Cultural organizations do not affect the performance of teachers Junior High School in District Comal Pemalang; 4) Organizational Culture moderate effect on the performance of teachers competence Junior High School, in District Comal Pemalang; 5) moderate the organizational culture employee motivation influences on teacher performance Junior High School in District Comal Pemalang. Theoretical implications and recommendations for future research are also discussed in the final part in this study.Keywords: Competence, Work Motivation, Organizational Culture and Teachers Performance